Analysis of the Implementation of Defense Expenditure Policy for Fiscal Year 2020 at the Ministry of Defense - Nanditya Putri Destyananda; Falih Suaedi; Erna Setijaningrum (Jurnal Administrasi Publik (Public Administration Journal), 2022)
This article aims to analyze the implementation of the defense spending policy in the fiscal year 2020 at the Ministry of Defense. The problem is focused on the success or failure of the implementation of defense spending policies in the fiscal year 2020 by using the theory of policy implementation by George C. Edward III. This study uses a qualitative approach with a descriptive method. The data were collected through documentation or literature study and analyzed qualitatively using an interactive model. This study concludes that the implementation of the defense spending policy has not been effective, especially in the procurement of the main weapon system equipment. This is a challenge faced by the Ministry of Defense. The procurement of the main weapons system can increase defense strength. However, the procurement of the main weapons system equipment that is still on raw materials from abroad shows the need for the development of the domestic defense industry. So support in the form of a larger budget and government commitment is very much needed so that the defense force can increase as well as the independence of the domestic defense industry can be realized immediately.